Medication adherence and its determinants amongst anti-hypertensive patients in a tertiary care hospital in Navi Mumbai - Badhe, Satyendra B.; Yadav, Pramila V.; Deolekar, Pradnya S.; Badhe, Suvarna B.; Aggarwal, Mihika (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Anti-hypertensive drugs can effectively control hypertension, subject to good adherence. Uncontrolled hypertension can lead to numerous complications, some even potentially fatal, such as myocardial infarction, atherosclerosis, thromboembolism, shock and stroke. Methods: A cross-sectional prospective study was conducted with the help of a pre-validated questionnaire during the course of 6 months in the medicine outpatient department and the inpatient department (wards) at a tertiary care hospital, Navi Mumbai in 200 hypertensive patients to calculate the correlation of the sociodemographic factors with adherence by the chi-squared test. Results: The overall percentage of adherence to antihypertensive medication was 34.8%. It was the highest (72.1%) in the younger age group, i.e., below 50 years. It was observed that as the age increases, the adherence to treatment decreases. Adherence rates were significantly higher among females and those individuals who had never attended school. Among the employed, 70.3% were adherent to their treatment and among the unemployed, 64.4% were adherent. The percentage of adherence was lower in alcohol consumers (9.5%) as compared to nonusers (76% and 32%, respectively). Conclusions: The clinician advising anti-hypertensive therapy should provide thorough counselling and stress on the issues created due to poor medication adherence as hypertension can be associated with severe outcomes. Treatments should be given in accordance with each patient’s lifestyles in mind such that they may continue taking their medications till the completion of their therapy.